2021
DOI: 10.3390/toxins13040265
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Multiple Peptides by Microcystin-Degrader Paucibacter toxinivorans (2C20)

Abstract: Since conventional drinking water treatments applied in different countries are inefficient at eliminating potentially toxic cyanobacterial peptides, a number of bacteria have been studied as an alternative to biological filters for the removal of microcystins (MCs). Here, we evaluated the degradation of not only MCs variants (-LR/DM-LR/-RR/-LF/-YR), but also non-MCs peptides (anabaenopeptins A/B, aerucyclamides A/D) by Paucibactertoxinivorans over 7 days. We also evaluated the degradation rate of MC-LR in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The literature on bacteria‐mediated microcystin degradation dates back to the 1990s (Jones et al 1994; Dziga et al 2017), and two primary pathways, the mlr + and mlr − , have been identified for microcystin biodegradation (Bourne et al 2001; Santos et al 2021). The mlr + biodegradation has been linked genetically to Sphingophyxis sp.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on bacteria‐mediated microcystin degradation dates back to the 1990s (Jones et al 1994; Dziga et al 2017), and two primary pathways, the mlr + and mlr − , have been identified for microcystin biodegradation (Bourne et al 2001; Santos et al 2021). The mlr + biodegradation has been linked genetically to Sphingophyxis sp.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, most cultures lack mcy genes and MC producing potential, but still encode for the synthesis of other secondary metabolites (Fig 3). A recent study has demonstrated the ability of mlr -bacteria to degrade both MCs and other cyanobacterial peptides (Santos et al, 2021) suggesting that associated bacteria within the WLECC may be capable of degrading other cyanopeptides beside MC through unknown pathways. Future research should address the substrate specificity of mlr- encoded enzymes, as well as cryptic pathways beyond mlr that can degrade MCs and/or other cyanobacterial peptides.…”
Section: Discussionmentioning
confidence: 99%